Greece : 2009 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that despite initial resilience partly explained by high wage growth and accelerated government spending in Greece, growth slowed substantially in early 2009. The main driving forces were lower investment and exports, destocking, and a decline in private consumption. Executive Directors have welcomed the extended period of strong growth through 2008, which had significantly narrowed the gap in real per-capita income with the EU-15. Directors have also emphasized the need to implement a comprehensive plan for fiscal consolidation and structural reform.